A method for preparing block copolymers by single electron transfer initiation

By using a low concentration of samarium diiodide/hexamethylphosphoryl triamine solution to initiate controllable radical polymerization to generate "active" radicals, the problems of side reactions and slow polymerization rates in the preparation of block copolymers are solved, and block copolymer preparation with controllable molecular weight, fast polymerization rates and suitable temperatures are achieved.

CN118930769BActive Publication Date: 2025-04-15NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411157266.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-04-15
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

In the prior art, the preparation of block copolymers has problems such as side reactions, slow polymerization rate, high polymerization temperature, high toxicity and high cost of the polymerization system.

Method used

The low concentration of samarium diiodide/hexamethylphosphoryl triamine solution is used to initiate controllable radical polymerization to generate negatively charged "active" radicals. The polymerization of olefin monomers is initiated through single electron transfer to achieve the preparation of block copolymers.

Benefits of technology

The molecular weight of the polymerization product is controlled, the molecular weight distribution is narrow, the polymerization rate is fast, close to the level of ordinary radical polymerization, and the polymerization can be carried out at a lower temperature, the reaction conditions are simple, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930769B_ABST
    Figure CN118930769B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing block copolymers by single electron transfer initiation, wherein the growth species of the method is a negatively charged free radical, which has the property of "activity", can accurately control the molecular weight of the polymer chain and obtain a polymer with a narrow molecular weight distribution, thereby obtaining a block copolymer with accurate structure. Based on the single electron transfer property of samarium diiodide, the free radical is negatively charged, and the charge repulsion inhibits the diradical termination of the free radical, which not only gives the free radical the property of "activity", but also keeps the polymerization system at a higher concentration of free radicals, so the polymerization rate is faster, close to the level of ordinary free radical polymerization, and is conducive to industrial production. The method of the present invention comprises the following steps: initiating controlled free radical polymerization with a low concentration of samarium diiodide / hexamethylphosphoric triamide solution; the concentration of samarium diiodide in the low concentration of samarium diiodide / hexamethylphosphoric triamide solution is 0.04-0.055 mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a block copolymer, and more particularly to a method for preparing the block copolymer by single electron transfer initiation. Background Art

[0002] Block copolymers are polymers formed by covalently linking two or more polymer chains with different properties. The components of this polymer are varied, and the molecular structure can be designed. The advantages of multiple polymers can be combined to produce polymer materials with excellent performance. The performance of polymer materials can be easily adjusted by selecting monomer units of different types and properties, or changing the chain length of each polymer. Block copolymers are widely used in the fields of elastomers, blending compatibilizers, dispersants and porous membrane preparation.

[0003] Methods for preparing block copolymers include anionic polymerization, controlled free radical polymerization, special initiator method and mechanochemical method. The propagating species of anionic polymerization and controlled free radical polymerization can maintain "activity". After the polymerization of the first monomer is completed, the second monomer can be added to continue polymerization, and the two polymer chains are connected by covalent bonds to form block copolymers. Due to the "active" nature of the propagating species, the molecular weight and molecular weight distribution of each segment in the block copolymer can be controlled, so anionic polymerization and controlled free radical polymerization are the main methods for preparing block copolymers. Although anionic polymerization has a fast polymerization rate and a narrow molecular weight distribution of the polymer product, due to the high activity and nucleophilicity of the anionic active species, the polymerization rate of polar monomers is often too fast and the polymerization is difficult to control. Monomers with electrophilic substituents (such as alkyl acrylates) are prone to side reactions such as chain termination or chain transfer under anion initiation, so this type of monomer is not easy to achieve anion-initiated block copolymerization. In recent years, controlled free radical polymerization has developed rapidly. Based on free radical propagating species, controlled free radical polymerization overcomes the above-mentioned problems of anionic polymerization. Controlled radical polymerization is mostly achieved by using the reversible dynamic equilibrium mechanism of active species / dormant species, such as nitroxide stabilized radical polymerization (NMP), atom transfer radical polymerization (ATRP) and reversible addition-fragmentation chain transfer polymerization (RAFT). For controlled radical polymerization, since the double radical termination of the radical is suppressed, the propagating radical can remain "active", making the molecular weight and molecular weight distribution of the radical polymerization product controllable. However, there are also some problems with the current controlled radical polymerization scheme. Based on the reversible dynamic equilibrium of active species / dormant species, and the equilibrium needs to be significantly biased towards the dormant species, the concentration of the propagating radical in the above controlled radical polymerization scheme is often too low, so its polymerization rate is usually much lower than that of ordinary radical polymerization. In addition, the NMP method is only applicable to styrene monomers, and the polymerization temperature is too high, exceeding 120°C; the initiator of the ATRP method is a halide, which has toxicity problems; the dithioester chain transfer agent of the RAFT method also has the disadvantage of high toxicity, and this type of chain transfer agent is high in cost and poor in stability. These problems limit the application field of controlled radical polymerization to a certain extent.

[0004] The redox potential of samarium diiodide is -1.55V. It is a typical single electron transfer reagent and is often used as a reducing agent in organic chemistry. Using this electron transfer ability, samarium diiodide can reduce a variety of organic compounds such as aldehydes, ketones and halides, and can also participate in conjugate addition, nucleophilic reactions, free radical cyclization, free radical coupling reactions and cascade reactions. Samarium diiodide is usually commercially available in the form of 0.1mol / L tetrahydrofuran solution. Due to the insufficient polarity of tetrahydrofuran, the reactivity of samarium diiodide is not high, but the addition of strong power supply reagents such as hexamethylphosphoric triamide and Lewis base can significantly improve the electron transfer ability of samarium diiodide. If the single electron transfer ability of samarium diiodide is used to initiate the polymerization of olefin monomers with samarium diiodide / hexamethylphosphoric triamide solution, a new method for preparing block copolymers by single electron transfer initiation can be developed and applied in the field of preparing block copolymers. Summary of the invention

[0005] The purpose of the present invention is to solve the problems and shortcomings of the prior art, such as the easy occurrence of side reactions, slow polymerization rate, high polymerization temperature, high toxicity of the polymerization initiation system, and high cost, and to provide a method for preparing block copolymers by single electron transfer initiation. The method for preparing block copolymers by single electron transfer initiation, in which the propagating species is a negatively charged free radical, has the property of "activity", can accurately control the molecular weight of the polymer chain and obtain a narrow molecular weight distribution polymers, thereby obtaining block copolymers with accurate structures. Based on the single electron transfer property of samarium diiodide, the free radical is negatively charged, and the charge repulsion inhibits the diradical termination of the free radical, which not only gives the free radical the property of "activity", but also keeps the polymerization system at a high concentration of free radicals. Therefore, the polymerization rate is fast, close to the level of ordinary free radical polymerization, which is conducive to industrial production. The polymerization can be carried out at a lower temperature, the reaction conditions are simple, and it is easy to achieve. The polymerization product has a wide range of uses in the fields of elastomers, blending compatibilizers, interface modifiers, dispersants, functionalized material surfaces and porous membrane preparation. The olefin monomer is activated and initiated with a samarium diiodide / hexamethylphosphoric triamide solution to produce "active" free radicals. After the polymerization of the previous monomer is completed, the "activity" of the free radical at the end of the polymer chain is still maintained, and the polymerization can continue by adding the second monomer, thereby obtaining a block copolymer. Block copolymers can be used more widely in the fields of elastomers, blending compatibilizers, interface modifiers, dispersants, functionalized material surfaces and porous membrane preparation.

[0006] The present invention is achieved through the following technical solutions:

[0007] The method for preparing block copolymers by single electron transfer initiation comprises the following steps: initiating controlled radical polymerization with a low concentration of samarium diiodide / hexamethylphosphoric triamide solution; the samarium diiodide concentration of the low concentration of samarium diiodide / hexamethylphosphoric triamide solution is 0.04-0.055 mol / L.

[0008] The method for preparing block copolymers by single electron transfer initiation of the present invention has a further technical scheme that the main steps are as follows: first, a samarium diiodide solution with a concentration of 0.1 mol / L is prepared using hexamethylphosphoric triamide as a solvent, and then hexamethylphosphoric triamide is added to dilute it to obtain a low-concentration samarium diiodide / hexamethylphosphoric triamide solution, and then a first olefin monomer is added to initiate polymerization, and after the polymerization is completed, a second olefin monomer is added to continue polymerization to obtain a block copolymer of two monomers. Within this low concentration range, the samarium diiodide / hexamethylphosphoric triamide solution can initiate controlled free radical polymerization, and the propagating free radical has the property of "activity", which is conducive to the preparation of block copolymers with accurate structures. When the concentration of samarium diiodide is higher than 0.055 mol / L, the propagating free radical is partially inactivated, and the polymerization product will show branching and gel phenomena, and these factors are not conducive to the preparation of block copolymers.

[0009] The method for preparing block copolymers by single electron transfer initiation of the present invention further comprises the following steps:

[0010] S1, adding sodium metal flakes to hexamethylphosphoric triamide to remove water, and then purifying by reduced pressure distillation;

[0011] S2, adding anhydrous sodium sulfate to the olefin monomer to remove water, and then purifying by reduced pressure distillation;

[0012] S3, under nitrogen atmosphere, adding measured samarium metal powder and iodine into the hexamethylphosphoric triamide purified in step S1, and after the reaction is completed, separating and preparing a 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution;

[0013] S4, under a nitrogen atmosphere, diluting the 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution prepared in step S3 with the hexamethylphosphoric triamide purified in step S1 to obtain a low concentration samarium diiodide / hexamethylphosphoric triamide solution, and then adding the first olefin monomer to initiate polymerization, and completing the polymerization of the first olefin monomer;

[0014] S5. Under nitrogen atmosphere, add a second olefin monomer to the reaction solution obtained in step S4 to continue polymerization to obtain a block copolymer of the two monomers.

[0015] The above-mentioned method for preparing block copolymers by single electron transfer initiation of the present invention has a further technical solution that the molar ratio of the metal samarium powder to the iodine used in step S3 is ≥6.5; the reaction is stirred at 85-95°C for more than 48 hours. A further technical solution is that the amount of the metal samarium powder used should be greater than the amount of iodine used. Taking the amount of hexamethylphosphoric triamide as 20mL, the amount of iodine used is 0.51g, i.e. 0.002mol, and the amount of the metal samarium powder used is 2.0g, i.e. 0.013mol. When preparing a samarium diiodide solution with a concentration of 0.1mol / L, due to heterogeneous reactions, the amount of metal samarium powder used should be significantly greater than the amount of iodine used.

[0016] A further technical solution of the method for preparing block copolymers by single electron transfer initiation of the present invention may be that when preparing the samarium diiodide / hexamethylphosphoric triamide solution with a concentration of 0.1 mol / L, the obtained samarium diiodide solution is the supernatant liquid for separating the remaining metal samarium powder.

[0017] A further technical solution of the method for preparing block copolymers by single electron transfer initiation of the present invention may be to complete the polymerization of the first olefin monomer as described in step S4, and the conversion rate thereof should reach more than 98%.

[0018] A further technical solution of the method for preparing block copolymers by single electron transfer initiation of the present invention may be that the polymerization temperature of the controlled radical polymerization of the olefin monomer is 50-60° C. Within this temperature range, the higher the temperature, the faster the polymerization rate.

[0019] The method for preparing block copolymers by single electron transfer initiation of the present invention can be further technically solved in that the first olefin monomer is methyl methacrylate, styrene, methyl acrylate or acrylic acid; the second olefin monomer is methyl methacrylate, acrylonitrile, methyl acrylate or acrylic acid. When preparing the block copolymer, the combination of the two monomers should be such that the Hammett parameter of the first olefin monomer is smaller than the value of the second olefin monomer.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The method for preparing block copolymers by single electron transfer initiation of the present invention uses a low concentration of samarium diiodide / hexamethylphosphoric acid triamide solution to initiate the polymerization of olefin monomers. Based on the single electron transfer ability of samarium diiodide, the growing active species is a negatively charged free radical with an "active" property. The polymerization belongs to controlled free radical polymerization, and the molecular weight of the polymerization product is controllable and the molecular weight distribution is narrow. Based on this "active" free radical, after the polymerization of the first monomer is completed, the polymerization can still be continued by adding the second monomer, thereby obtaining a block copolymer. The polymerization can be terminated by a free radical inhibitor, such as 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH), oxygen and benzoquinone. The amount of growing free radicals (~10 -4 mol / L), the theoretical molecular weight calculated based on this is consistent with the experimental molecular weight tested by GPC, confirming the free radical process of the polymerization. When the polymerization is carried out in a high-voltage DC electric field, the polymer is biased toward the anode side, indicating that the growing free radicals are negatively charged. In other words, due to the repulsion of the same charge, the double radical termination of the free radical is suppressed, which not only gives the free radical the property of "activity", but also enables the polymerization system to maintain a higher concentration of growing free radicals (~10 -4 mol / L), which is much higher than the steady-state free radical concentration of ordinary free radical polymerization (~10 -8 mol / L), so the polymerization rate is fast, close to the level of ordinary free radical polymerization. When a small amount of water is added to the polymerization system, the polymerization is accelerated instead of inhibited, showing the solvent effect of water acceleration, indicating that the polymerization is not initiated by anions. Specifically: (1) The growing species of the polymerization of the present invention is a negatively charged free radical, which has the property of "activity". After the polymerization of the first monomer is completed, the second monomer can be added to continue the polymerization to obtain a block copolymer of the two monomers; (2) Based on this "active" free radical, the molecular weight of the polymer segment can be accurately controlled by adjusting the polymerization time or the monomer conversion rate. At the same time, the molecular weight distribution of the polymer segment is narrow, and a block copolymer with accurate structure is obtained; (3) Since the concentration of the growing free radicals in the polymerization system is high, the polymerization rate is fast, close to the level of ordinary free radical polymerization, which is conducive to industrial production; (4) The polymerization is carried out at a relatively low temperature, and the polymerization conditions are simple and easy; (5) The block copolymer products have a wide range of uses in the fields of elastomers, blending compatibilizers, interface modifiers, dispersants, functionalized material surfaces and porous membrane preparation. DETAILED DESCRIPTION

[0022] The basic steps of the method for preparing block copolymers by single electron transfer initiation in the embodiment are as follows:

[0023] S1, adding sodium metal flakes to hexamethylphosphoric triamide to remove water, and then purifying by reduced pressure distillation;

[0024] S2, adding anhydrous sodium sulfate to the olefin monomer to remove water, and then purifying by reduced pressure distillation;

[0025] S3, under nitrogen atmosphere, adding measured samarium metal powder and iodine to the hexamethylphosphoric triamide purified in step S1, stirring and reacting at 85-95° C. for more than 48 hours, and preparing a 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution by separation; the molar ratio of samarium metal powder to iodine is ≥6.5;

[0026] S4, under a nitrogen atmosphere, diluting the 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution prepared in step S3 with the hexamethylphosphoric triamide purified in step S1 to obtain a low concentration samarium diiodide / hexamethylphosphoric triamide solution, and then adding the first olefin monomer to initiate polymerization, and completing the polymerization of the first olefin monomer, and the conversion rate should reach more than 98%;

[0027] S5. Under nitrogen atmosphere, add a second olefin monomer to the reaction solution obtained in step S4 to continue polymerization to obtain a block copolymer of the two monomers.

[0028] Example 1

[0029] 2.0g of samarium metal powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 5mL of hexamethylphosphoric triamide was mixed with 5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.05mol / L, and then 2mL of styrene was added to initiate polymerization at 60°C. After the polymerization of styrene was completed, 2mL of methyl methacrylate was added, and the polymerization was continued at 60°C to obtain a block copolymer of styrene-methyl methacrylate. The results are shown in Table 1.

[0030] Example 2

[0031] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 4.5mL of hexamethylphosphoric triamide was mixed with 5.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.055mol / L, and then 2mL of styrene was added to initiate polymerization at 60°C. After the polymerization of styrene was completed, 2.5mL of acrylic acid was added, and the polymerization was continued at 60°C to obtain a block copolymer of styrene-acrylic acid. The results are shown in Table 1.

[0032] Example 3

[0033] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 95°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 5mL of hexamethylphosphoric triamide was mixed with 5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.05mol / L, and then 2mL of styrene was added to initiate polymerization at 60°C. After the polymerization of styrene was completed, 2mL of acrylonitrile was added, and the polymerization was continued at 60°C to obtain a block copolymer of styrene-acrylonitrile. The results are shown in Table 1.

[0034] Example 4

[0035] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 85°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 4.5mL of hexamethylphosphoric triamide was mixed with 5.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.055mol / L, and then 2mL of styrene was added to initiate polymerization at 60°C. After the polymerization of styrene was completed, 2mL of methyl acrylate was added, and the polymerization was continued at 60°C to obtain a block copolymer of styrene-methyl acrylate. The results are shown in Table 1.

[0036] Example 5

[0037] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 88°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 6mL of hexamethylphosphoric triamide was mixed with 4mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.04mol / L, and then 1mL of methyl acrylate was added to initiate polymerization at 50°C. After the polymerization of methyl acrylate was completed, 1.5mL of acrylonitrile was added, and the polymerization was continued at 50°C to obtain a block copolymer of methyl acrylate-acrylonitrile. The results are shown in Table 1.

[0038] Example 6

[0039] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 93°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 4.5mL of hexamethylphosphoric triamide was mixed with 5.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.055mol / L, and then 2mL of acrylic acid was added to initiate polymerization at 60°C. After the polymerization of acrylic acid was completed, 3mL of acrylonitrile was added, and the polymerization was continued at 60°C to obtain a block copolymer of acrylic acid-acrylonitrile. The results are shown in Table 1.

[0040] Example 7

[0041] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 87°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 5.5mL of hexamethylphosphoric triamide was mixed with 4.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.045mol / L, and then 1.5mL of methyl acrylate was added to initiate polymerization at 55°C. After the polymerization of methyl acrylate was completed, 2mL of acrylonitrile was added, and the polymerization was continued at 55°C to obtain a block copolymer of methyl acrylate-acrylonitrile. The results are shown in Table 1.

[0042] Example 8

[0043] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 4.5mL of hexamethylphosphoric triamide was mixed with 5.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.055mol / L, and then 2mL of methyl methacrylate was added to initiate polymerization at 60°C. After the polymerization of methyl methacrylate was completed, 2mL of acrylonitrile was added, and the polymerization was continued at 60°C to obtain a block copolymer of methyl methacrylate-acrylonitrile. The results are shown in Table 1.

[0044] Comparative Example 1

[0045] 2.0g of samarium metal powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 7mL of hexamethylphosphoric triamide was mixed with 3mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a 0.03mol / L samarium diiodide solution, and then 2mL of styrene was added to initiate polymerization at 60°C. Due to the low polymerization rate and high viscosity of the system, the conversion rate of polystyrene was difficult to reach more than 98%, and the block copolymer of styrene-methyl methacrylate was not successfully prepared.

[0046] Comparative Example 2

[0047] 2.0g of metal samarium powder and 0.51g of iodine were added to 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 9.5mL of hexamethylphosphoric triamide was mixed with 0.5mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.005mol / L, 2mL of methyl methacrylate was added, and polymerization was initiated at 60°C, but no polymerization product was obtained. 2mL of acrylonitrile was added, but still no polymerization product was obtained.

[0048] Comparative Example 3

[0049] 2.0g of samarium metal powder and 0.51g of iodine were put into 20mL of hexamethylphosphoric triamide, stirred and reacted at 90°C for 48 hours, and a 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution was prepared by separation. 1mL of hexamethylphosphoric triamide was mixed with 9mL of 0.1mol / L samarium diiodide / hexamethylphosphoric triamide solution, diluted to obtain a samarium diiodide solution with a concentration of 0.09mol / L, and then 2mL of methyl methacrylate was added to initiate polymerization at 60°C. After the polymerization of methyl methacrylate was completed, 2mL of acrylonitrile was added, and polymerization was continued at 60°C to obtain a block copolymer of methyl methacrylate-acrylonitrile, and the results are shown in Table 1. According to GPC analysis, the homopolymer of methyl methacrylate (before adding acrylonitrile) and the block copolymer of methyl methacrylate-acrylonitrile both showed shoulder peaks on the high molecular weight side, indicating that side reactions such as grafting occurred in the polymerization, and no block copolymer with accurate structure could be obtained.

[0050] Table 1 Number average molecular weight of block copolymers Value and block composition

[0051]

[0052] Note: Component 1 is the first monomer added during block copolymerization, component 2 is the second monomer, and the component contents are mol%.

[0053] From the above results, it can be seen that according to the method for preparing block copolymers by single electron transfer initiation of the present invention, the polymerization of olefin monomers is initiated by using a low concentration of 0.04-0.055 mol / L samarium diiodide / hexamethylphosphoric acid triamide solution, and block copolymers can be obtained in Examples 1-8. This shows that the active species generated by the low concentration of samarium diiodide / hexamethylphosphoric acid triamide solution has the property of "activity". After the previous monomer is consumed, the addition of the second monomer can continue polymerization to form a block copolymer. The molecular weight distribution of the obtained block copolymer is relatively narrow. The molecular weight and block composition of the block copolymer can be precisely adjusted by changing the feeding amount of the monomer and the conversion rate of the second monomer. The polymerization of Examples 1 to 8 can be terminated by DPPH, but not by water, indicating that the propagating species is a free radical. When the polymerization is carried out in a high-voltage DC electric field, the polymer is biased toward the anode side, indicating that the propagating free radical is negatively charged. It is precisely because of this charge repulsion that the diradical termination of the free radical is suppressed, giving the propagating free radical the property of "activity". Based on this negatively charged propagating free radical, when preparing the block copolymer, the Hammett parameter of the first olefin monomer used should be less than the value of the second olefin monomer.

[0054] Compared with Example 1, Comparative Example 1 uses a samarium diiodide / hexamethylphosphoric acid triamide solution with a concentration (0.03 mol / L) lower than 0.04 mol / L to initiate the preparation of a block copolymer of styrene-methyl methacrylate. Due to the low concentration of samarium diiodide, the concentration of the obtained propagating free radicals is also low, so the polymerization rate is slow. At the same time, the molecular weight of polystyrene is large and the viscosity of the system is too large. The conversion rate of polystyrene is difficult to reach more than 98%, and the block copolymer of styrene-methyl methacrylate cannot be successfully prepared. Comparative Example 2 uses a samarium diiodide / hexamethylphosphoric acid triamide solution with a lower concentration (0.005 mol / L) to initiate the polymerization. No polymerization product is produced, indicating that the initiation is invalid, which may be caused by the low concentration of samarium diiodide being consumed by a small amount of impure substances remaining in the polymerization system. Compared with Example 8, Comparative Example 3 uses a samarium diiodide / hexamethylphosphoric acid triamide solution with a concentration higher than 0.055 mol / L to initiate the preparation of a block copolymer of methyl methacrylate-acrylonitrile. According to GPC analysis, the homopolymer of methyl methacrylate (before adding acrylonitrile) and the block copolymer of methyl methacrylate-acrylonitrile both have shoulder peaks on the high molecular weight side, indicating that side reactions such as grafting and branching occur in the polymerization, and a block copolymer with accurate structure cannot be obtained. The polymerization of Comparative Example 3 is not inhibited by DPPH, and water is an inhibitor, indicating that its polymerization is not initiated by free radicals. Comparative Example 3 has the ability to initiate the polymerization of non-olefin monomer ε-caprolactone. Considering the single electron transfer property of samarium diiodide, the polymerization of Comparative Example 3 should be anion initiated. These results show that a low concentration of samarium diiodide / hexamethylphosphoric acid triamide solution (0.04-0.055 mol / L) has the ability to initiate free radical polymerization, while samarium diiodide has the ability to initiate anionic polymerization at high concentrations. In the anionic polymerization of methyl methacrylate, the nucleophilic anionic active species easily attack the carbonyl group within or between molecules, causing side reactions such as branching, chain termination and cyclization, so that a block copolymer with accurate structure cannot be obtained. The molecular weight of the block copolymer obtained in Comparative Example 3 is particularly low, which may be caused by the high concentration of the growing anion, or may be related to the above-mentioned side reactions.

[0055] The above results show that the method for preparing block copolymers by single electron transfer initiation of the present invention utilizes the single electron transfer ability of a low concentration of samarium diiodide / hexamethylphosphoric triamide solution to initiate the negatively charged free radicals generated by olefin monomers to have "active" properties, thereby obtaining block copolymers with accurate structures.

Claims

1. A method for preparing a block copolymer by single electron transfer initiation, characterized in that: The following steps are involved: The block copolymer is prepared by initiating olefin monomers with a low concentration of samarium diiodide / hexamethylphosphoric triamide solution, wherein the propagating species are negatively charged free radicals; the samarium diiodide concentration of the low concentration of samarium diiodide / hexamethylphosphoric triamide solution is 0.04-0.055 mol / L.

2. The method for preparing block copolymers by single electron transfer initiation according to claim 1, characterized in that: The main steps are as follows: first, a samarium diiodide solution with a concentration of 0.1 mol / L is prepared using hexamethylphosphoric triamide as a solvent, and then hexamethylphosphoric triamide is added to dilute it to obtain a low concentration of samarium diiodide / hexamethylphosphoric triamide solution, and then a first olefin monomer is added to initiate polymerization. After the polymerization is completed, a second olefin monomer is added to continue polymerization to obtain a block copolymer of the two monomers.

3. The method for preparing block copolymers by single electron transfer initiation according to claim 2, characterized in that: The following steps are involved: S1, adding sodium metal flakes to hexamethylphosphoric triamide to remove water, and then purifying by reduced pressure distillation; S2, adding anhydrous sodium sulfate to the olefin monomer to remove water, and then purifying by reduced pressure distillation; S3, under nitrogen atmosphere, adding measured samarium metal powder and iodine into the hexamethylphosphoric triamide purified in step S1, and after the reaction is completed, separating and preparing a 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution; S4, under a nitrogen atmosphere, diluting the 0.1 mol / L samarium diiodide / hexamethylphosphoric triamide solution prepared in step S3 with the hexamethylphosphoric triamide purified in step S1 to obtain a low concentration samarium diiodide / hexamethylphosphoric triamide solution, and then adding the first olefin monomer to initiate polymerization, and completing the polymerization of the first olefin monomer; S5. Under nitrogen atmosphere, add a second olefin monomer to the reaction solution obtained in step S4 to continue polymerization to obtain a block copolymer of the two monomers.

4. The method for preparing block copolymers by single electron transfer initiation according to claim 3, characterized in that: The molar ratio of the samarium metal powder to the iodine in step S3 is ≥ 6.5; the reaction is carried out by stirring at 85-95° C. for more than 48 hours.

5. The method for preparing block copolymers by single electron transfer initiation according to claim 4, characterized in that: The amount of the samarium metal powder used should be greater than the amount of iodine used. Based on 20 mL of hexamethylphosphoric triamide, the amount of iodine used is 0.51 g, i.e., 0.002 mol, and the amount of the samarium metal powder used is 2.0 g, i.e., 0.013 mol.

6. The method for preparing block copolymers by single electron transfer initiation according to claim 3, characterized in that: When preparing the samarium diiodide / hexamethylphosphoric acid triamide solution with a concentration of 0.1 mol / L, the obtained samarium diiodide solution is the supernatant liquid for separating the remaining metal samarium powder.

7. The method for preparing block copolymers by single electron transfer initiation according to claim 3, characterized in that: The polymerization of the first olefinic monomer described in step S4 is completed with a conversion rate of more than 98%.

8. The method for preparing block copolymers by single electron transfer initiation according to claim 3, characterized in that: The polymerization temperature of the controlled free radical polymerization of the olefin monomer is 50-60°C.

9. The method for preparing block copolymers by single electron transfer initiation according to claim 3, characterized in that: The first olefin monomer is methyl methacrylate, styrene, methyl acrylate or acrylic acid; the second olefin monomer is methyl methacrylate, acrylonitrile, methyl acrylate or acrylic acid.

Citation Information

Patent Citations

  • Method for preparing segmented copolymer through solvation electron initiation

    CN115785356A

  • Controllable free radical polymerization method initiated by solvation electrons

    CN115894755A